The conflict over the privatization of JAPDEVA`s ports in the Costa Rican press (2010-2011) - Díaz González, José Andrés (2015)
This paper analyzes the content of the news published by four newspapers: Semanario Universidad, El País, Diario Extra and La Nación, in relation with the process of privatization of ports, managed by the Junta de Administración Portuaria y Desarrollo Económica de la Vertiente Atlántica (JAPDEVA). It concluded the existence of two discourses in the news content. The first one supports the privatization process and, the second one advocates for a port modernization process without privatization. Both discourses exclude or conceal the underlying problems that have led to the conflict and do not communicate the actions and opinions of port workers and Costa Rican population regarding this conflict.